Study of a self-compacting fiber-reinforced concrete to be applied in the precast industry - Paulo, Fernandes (2019)
This paper describes an experimental program designed to obtain a self-compacting fber-reinforced concrete formulation based on the Faury’s reference curve, suitable to develop new solutions of non-structural slender precast elements in buildings. In the present work, it was possible to delimit the main parameters that allow to obtain a self-compacting concrete with high early age strength, allowing its application in the precast industry increasing the production cycles. The program has shown also the importance of the compatibility between the cement and the superplasticizer to prevent the undesirable efects of the high dosages of admixture in the fresh concrete performance, such as segregation and air content. The experimental campaign consisted in fve self-compacting concrete mixes and another fve self-compacting fber-reinforced concrete. The frst ones aimed to optimize parameters such as water/cement ratio, superplasticizer, and binder dosages in a plain SCC. Afterwards, these parameters were re-evaluated in another fve mixes due to the impact of the fbers in the concrete’s fresh performance. The slump fow and the compressive strength at diferent ages (1, 7, and 28 days) were evaluated for all mixes.